CENPN contributes to pancreatic carcinoma progression through the MDM2-mediated p53 signaling pathway - Ming Xu; Jie Tang; Qiong Sun; Jing Meng; Guoyu Chen; Yunli Chang; Yao Yao; Jieru Ji; Hao Luo; Lingling Chen; Minxue Lu; Weiwei Shi (Archives of Medical Science)
Introduction We undertook an in-depth investigation of the data pertaining to pancreatic adenocarcinoma (PAAD) to identify potential targets for the development of precision therapies.